Manajemen Stakeholder Kelompok Sadar Wisata dalam Pengembangan Wisata Budaya di Desa Rancakalong Sumedang - Syedira, Sedranda; Widiowati, Didiet (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2024)
This community service is motivated by the collaboration between the Sumedang Regency Government and the Bandung Social Welfare Polytechnic through the implementation of community-based practicum targeting the Key Performance Indicators (IKU) listed in the Sumedang Regency Regional Development Work Plan concerning four issues, one of which is increasing village competitiveness in the form of one village one product. Based on the potential and assets of the community in the Rancakalong Village area, community service is directed at efforts to develop culture-based tourism. The methods carried out in community service practice are participatory methods, including Focus Group Discussion (FGD), interviews, observations, and documentation studies. Through stakeholder management of tourism awareness groups, service practices are directed to see the extent of the involvement of figures which then emerges the commitment of figures in efforts to develop cultural tourism. The results of this community service activity are in the form of actor quadrant mapping which shows four kinds of stakeholder positions based on their interests and influences, the output of which is in the form of restructuring tourism awareness groups and preparing group work plans.